Understanding the 'Sinhala- Buddhist' Movement in Sri Lanka - Antony Fernando (Journal of Dharma, 1995)
When Pope John Paul II visited Sri Lanka in January 'this year, the decision taken by the Buddhist clergy not to participate in any ceremony organized for his welcome was considered an event big enough to be reported in all the major newspapers of the world. In fact the decision was very unusual, because Buddhists generally are reputed for their non-aggressiveness and for their tolerance towards other religions. The characteristic virtue of Buddhism is benevolence or friendliness (maitriya). The decision of the Buddhist clergy was all the more striking because representatives of all the other religions such as Hinduism and Islam as also of all other Christian denominations were present at the public reception given to the Pope.